2021
DOI: 10.3389/fonc.2020.625633
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger Protein CTCF Regulates Extracellular Matrix (ECM)-Related Gene Expression Associated With the Wnt Signaling Pathway in Gastric Cancer

Abstract: Gastric cancer (GC), a leading cause of cancer-related death, is a heterogeneous disease. We aim to describe clinically relevant molecular classifications of GC that incorporate heterogeneity and provide useful clinical information. We combined different gene expression datasets and filtered a 7-gene signature related to the extracellular matrix (ECM), which also exhibited significant prognostic value in GC patients. Interestingly, putative CCCTC-binding factor (CTCF) regulatory elements were identified within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(33 reference statements)
3
11
0
Order By: Relevance
“…Our study identified the TME-related gene PLXDC2 in a highstromal population and had a prognostic signature correlated to the CD163 M2 macrophages, further promoting EMT markers. Similar to the previous reporting that stromal EMT gene signature affects GC prognosis and immunotherapy responsiveness (Zheng and Li, 2020;Liu et al, 2021). The combined PLXDC2/EMT/M2 macrophages axis may affect GC outcome and immunotherapy responsiveness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study identified the TME-related gene PLXDC2 in a highstromal population and had a prognostic signature correlated to the CD163 M2 macrophages, further promoting EMT markers. Similar to the previous reporting that stromal EMT gene signature affects GC prognosis and immunotherapy responsiveness (Zheng and Li, 2020;Liu et al, 2021). The combined PLXDC2/EMT/M2 macrophages axis may affect GC outcome and immunotherapy responsiveness.…”
Section: Discussionsupporting
confidence: 88%
“…Our study confirmed this previous finding and identified a new EMT-related function for PLXDC2. Epithelial-mesenchymal transition in GC have been discussed in previous studies of our lab, and this study extended our understanding of EMT in GC (Liu et al, 2021). The function of our key gene in EMT may indicate that PLXDC2 is a regulator of tumor metastasis.…”
Section: Discussionsupporting
confidence: 69%
“…Liu et al 20 found that high or low expression of ECMrelated genes revealed different levels of tumour aggressiveness, and the zinc finger protein CTCF regulates ECM-related genes, thereby promoting GC cell growth and migration. Wei et al 21 found that HOTAIR and COL5A1 were overexpressed in GC compared to normal controls, and HOTAIR regulates GC growth by sponging miR-1277-5p and upregulating COL5A1 via effects on the tumour microenvironment.…”
mentioning
confidence: 99%
“…Collagen type I α 1 (COL1A1) is a member of collagen family and collagen is the most abundant protein of extracellular matrix (ECM) being naturally present in human tissues such as skin, bones, cartilage, tendon and ligaments. This biopolymer interacts with cells and regulates cell anchorage, migration, proliferation and survival ( 16 , 17 ). In the cardiovascular system, COL1A1 and its related signaling pathways are primarily associated with cardiac development and a variety of diseases processes.…”
Section: Introductionmentioning
confidence: 99%